FITTING ISOCHRONE OF HYADES STAR CLUSTER BY BUILDING COLOUR MAGNITUDE DIAGRAM (CMD) - Annisa Novia Indra Putri (Journal of Science and Applicative Technology, 2018)
Star cluster sky survey from many projects have many informations about our Galaxy, Milky Way. Hyades star cluster is the nearest open cluster and one of the best-studied star cluster. Its location about 153 light-years away from the Solar System consist of roughly spherical group of hundreds of stars. Earlier information from this cluster can be used to constraint other paramaters such as structuer, composition, dynamic formation, and evolution of Galaxy. Aim this research is fitting model of simple Colour Magnitude Diagram (CMD) with isochrone from Hyades data using monte caro method including binary star fraction effect and fotometry uncertainty. Basic parameter Hyades data is taken from WEBDA while isochrone Hyades data is taken from Padova site. The result from this research is limiting magnitude instrument observing Hyades around 16 mag. There is points of Hyades data forming new main sequence under real main sequence which fit with model.